CXCL12 Modulates Prostate Cancer Cell Adhesion by Altering the Levels or Activities of β1-Containing Integrins - Mehdi Dehghani; Sedigheh Kianpour; Ana Zangeneh; Zohreh Mostafavi-Pour (International Journal of Cell Biology)
The mechanisms by which prostate cancer (PCa) cell adhesion and migration are controlled during metastasis are not well understood. Here, we studied the effect of CXCL12 in PCa cell adhesion and spreading in DU145 and PC3 cell lines using as substrates collagen I, fibronectin (FN), and their recombinant fragments. CXCL12 treatment increased β1 integrin-dependent PC3 cell adhesion on FN which correlated with increased focal adhesion kinase activation. However neither α5β1 nor α4β1 subunits were involved in this adhesion. By contrast, CXCL12 decreased DU145 adhesion and spreading on FN by downregulating α5 and β1 integrin expression. To demonstrate the clinical relevance of CXCL12 in PCa, we measured CXCL12 levels in plasma by using ELISA and found that the chemokine is elevated in PCa patients when compared to controls. The high concentration of CXCL12 in patients suffering from PCa in comparison to those with benign disease or healthy individuals implicates CXCL12 as a potential biomarker for PCa. In addition these data show that CXCL12 may be crucial in controlling PCa cell adhesion on fibronectin and collagen I, possibly via crosstalk with integrin receptors and/or altering the expression levels of integrin subunits.